AN REVIEW FOR THE IMPLEMENTATION OF HUMAN RIGHTS IN INDIA: A STUDY - Kumar, Pradeep; Rajneesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Human rights are fundamental rights and freedoms that are inherent to all human beings, regardless of race, nationality, ethnicity, language, religion, or any other status. These rights are considered universal, inalienable, and indivisible. They encompass a broad range of principles and values aimed at ensuring dignity, equality, and justice for every individual. The concept of human rights has evolved over centuries and is enshrined in various international documents, including the Universal Declaration of Human Rights (UDHR) adopted by the United Nations General Assembly in 1948. The UDHR serves as a foundational document outlining the basic rights and freedoms to which all human beings are entitled. Every individual has the right to life, liberty, and security of person. Individuals have the right to express their opinions, beliefs, and ideas freely, without censorship or restraint. All human beings are equal in dignity and rights, regardless of factors such as race, gender, religion, or social status. Right to education: Everyone has the right to education, which should be free, compulsory, and directed to the full development of the human personality. Individuals should not be discriminated against on the basis of race, ethnicity, gender, religion, disability, or any other status. Every person has the right to a fair and public trial by an impartial tribunal. Right to work and just and favorable conditions of work: Everyone has the right to work, to free choice of employment, and to just and favorable conditions of work.Right to freedom from torture and cruel, inhuman, or degrading treatment or punishment: No one shall be subjected to torture or to cruel, inhuman, or degrading treatment or punishment. These are just a few examples of the many human rights recognized and protected by international law. Governments, international organizations, and civil society groups play crucial roles in promoting and protecting human rights, both domestically and globally. Despite progress in many areas, violations of human rights continue to occur in various parts of the world, underscoring the ongoing importance of advocacy, education, and activism in advancing the cause of human rights.